Experimental Investigation of a Novel CFRP-Steel Composite Tube-Confined Seawater-Sea Sand Concrete Intermediate Long Column - Fu, Hao; Guo, Kangle; Wu, Zhaojun; Mai, Rihao; Chin, Chee Loong; Ma, Chau-Khun (International Journal of Integrated Engineering, 2024)
In order to fully utilize sea sand in offshore engineering, a novel carbon fiber-reinforced polymer (CFRP)-steel composite tube-confined seawater-sea sand concrete (FCTSSC) column structure has been developed. This study conducts experimental investigations on FCTSSC intermediate long columns for the first time. It investigates the failure modes and the impact of the external CFRP layers number on the axial compression performance. The results reveal that the FCTSSC intermediate long column specimens exhibit the failure modes of global buckling and localized steel tube bulging. After CFRP restriction, the ultimate load bearing capacity of the specimens increased from 12.51% to 20.87%. The ultimate load bearing capacity, its enhancement percentage, and peak lateral deformation are all positively correlated with the external CFRP layers number. Finally, a summary and assessment were conducted on the applicability and accuracy of the existing load bearing capacity models, providing a reference for subsequent research.